2010
DOI: 10.1016/j.ygyno.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy during endometrial cancer staging: Practice patterns among gynecologic oncologists

Abstract: Objectives Several controversies surround lymphadenectomy for endometrial cancer; surgical approach, who to stage, and the anatomic borders of the lymphadenectomy. The purpose of this study was to identify practice patterns among gynecologic oncologists when performing a lymph node evaluation during staging for endometrial cancer. Methods A self-administered survey was sent via email to all SGO members on 3 occasions between 2/09 and 4/09. The survey addressed surgical approach, algorithms used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 17 publications
0
82
1
3
Order By: Relevance
“…The problem is how to determine those patients. Although standard treatment for women with endometrial cancer included a comprehensive staging surgery consisting of total abdominal hysterectomy and bilateral salpingo-oophorectomy with pelvic and para-aortic lymph node dissection, several studies published over the past several years have questioned the necessity of such a comprehensive surgery for most of the patients with endometrial cancer (7,8,(16)(17)(18)(19). Mariani and coworkers demonstrated that patients with endometrioid type Grade 1 or 2 disease with no or superficial myometrial invasion have a negligible risk for lymphatic metastasis when the tumor diameter is 2 cm or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is how to determine those patients. Although standard treatment for women with endometrial cancer included a comprehensive staging surgery consisting of total abdominal hysterectomy and bilateral salpingo-oophorectomy with pelvic and para-aortic lymph node dissection, several studies published over the past several years have questioned the necessity of such a comprehensive surgery for most of the patients with endometrial cancer (7,8,(16)(17)(18)(19). Mariani and coworkers demonstrated that patients with endometrioid type Grade 1 or 2 disease with no or superficial myometrial invasion have a negligible risk for lymphatic metastasis when the tumor diameter is 2 cm or less.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical staging procedure includes total hysterectomy with bilateral salpingo-oophorectomy and bilateral pelvic and para-aortic lymph node dissection (5). However, approximately 75% of patients with endometrioid type adenocarcinoma of endometrium is confined to the uterus at the time of diagnosis and a more conservative surgery may be considered for those (6,7). Patients with certain well-defined pathologic features are classified as low-risk for extrauterine disease and lymph node spread.…”
mentioning
confidence: 99%
“…The robotic approach could be a 'benefit' in obese women. (Boggess, 2008], but access to the high para-aortic area appears to be limited compared with the laparoscopic or open surgical approaches [Soliman, 2010]. When surgery is not feasible due to medical contraindications (5-10% of patients), external radiation therapy with or without intracavitary brachytherapy to the uterus and vagina is suitable for individual clinical use [Colombo, 2011].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…(Susumu, 2008) Platinum-based chemotherapy can be considered in this stage. In retrospective series that platinum-based adjuvant chemotherapy for stage II disease improves PFS and overall survival [Soliman, 2010].…”
Section: Surgical Treatment In Stage II Endometrial Cancermentioning
confidence: 99%
“…Traditional staging via lymphadenectomy for uterine cancers involves the removal of pelvic and paraaortic lymph nodes, which has been associated with increased morbidity including lower extremity lymphedema and lymphocyst formation. [7][8][9][10] Recently, however, sentinel lymph node (SLN) mapping has gained greater attention. 11,12 While its role in endometrial cancer remains undetermined, a significant amount of literature has accrued testifying to the benefit it may provide patients through equivalent detection of metastatic disease with lesser morbidity than standard lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%